2012
DOI: 10.1002/macp.201200165
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Computational and Experimental Study on the Free‐Radical Copolymerization of Styrene and Hydroxyethyl Acrylate

Abstract: Bulk free‐radical copolymerization of styrene and 2‐hydroxyethyl acrylate (HEA) is investigated experimentally at 50 °C using pulsed‐laser polymerization and computationally using ab initio simulations. Arrhenius parameters for HEA chain‐end homopropagation are A = 1.72 × 107 L mol−1 s−1 and Ea = 16.8 kJ mol−1, based on experiments between 20 and 60 °C. Copolymer composition data are well fitted by the terminal model with reactivity ratios rST = 0.44 ± 0.03 and rHEA = 0.18 ± 0.04, but the variation in the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…assumed to be adequately described by the BA coefficients. The changes to propagation kinetics due to H‐bonding and solvent effects present in HEA (co)polymerizations were set as determined by PLP‐SEC studies, with HEA homopropagation kinetics taken from previous investigation that showed a 20% increase in k p over the BA value . HEA/BMA reactivity ratios were determined to be solvent dependent, leading to the two sets of values determined in ketones (set a) and bulk (set b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…assumed to be adequately described by the BA coefficients. The changes to propagation kinetics due to H‐bonding and solvent effects present in HEA (co)polymerizations were set as determined by PLP‐SEC studies, with HEA homopropagation kinetics taken from previous investigation that showed a 20% increase in k p over the BA value . HEA/BMA reactivity ratios were determined to be solvent dependent, leading to the two sets of values determined in ketones (set a) and bulk (set b).…”
Section: Resultsmentioning
confidence: 99%
“…For relative molar masses, polystyrene standards between 870 and 875 000 g mol −1 were used for the calibration of the separation performed by 4 Styragel columns (HR 0.5, 1, 3, 4) maintained at 35 °C, with a sample solution flowrate of 0.3 mL min −1 . Proper transformation of relative molar masses with known Mark–Houwink parameters allows for a suitable comparison and verification between RI and LS results, as reported elsewhere; all MW results presented are from RI detection, due to the superior signal to noise response.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…11,12 We have been systematically studying the influence of the hydroxyl functionality on polymerization kinetics, generally introduced to systems through addition of 2-hydroxyethyl acrylate (HEA) or 2-hydroxyethyl methacrylate (HEMA) monomers, but also possibly through solvent choice. The interaction between the hydroxyl hydrogen and the carbonyl oxygen of the acrylic ester reduces the electron density at the double bond to increase its reactivity, as detected through infrared spectroscopy; 21,22 thus, the kp value for HEMA in bulk 23 is found to be higher than that of butyl methacrylate (BMA) by a factor of 2.5. Hydrogen-bonding also leads to concentration-dependent kp in aqueous systems, 24 as well as a modified relative reactivity in copolymerization, as has been demonstrated for the most prominent systems involving hydroxyl-functional HEA or HEMA 8,22 and carboxyl-functional acrylic acid or methacrylic acid (AA/MAA).…”
Section: Introductionmentioning
confidence: 99%
“…reversible additionfragmentation chain transfer, pulsed-laser polymerization, radical emulsion polymerization, iodide-mediated radical polymerization, living anionic copolymerization, free radical copolymerization, successive photo-induced charge-transfer polymerization, atom transfer radical polymerization and nitroxide-mediated polymerization. The copolymers containing polystyrene segments have been copolymerized using free radical polymerization with maleic anhydride, 10 divinylbenzene, 11,12 methyl methacrylate, 13,14 hydroxyethyl acrylate, 15 acrylonitrile, 16 butyl acrylate, 17,18 acrylic acid, 19 acrylic acid-styrene sulfonic acid 20 and vinyl acetate. 21 A copolymer of 2,2-dimethyl-5-methylene-1,3-dioxolan-4-one has been synthesized with methyl methacrylate, vinyl acetate and styrene using free radical copolymerization, resulting in higher molecular weight copolymers containing poly(2,2dimethyl-5-methylene-1,3-dioxolan-4-one), poly( -hydroxyacrylic acid) [22][23][24] and its derivative segments.…”
Section: Introductionmentioning
confidence: 99%